Propuesta Urbana para la Integración del Asentamiento Humano “Los Ángeles” a la ciudad de Huaquillas. - Guamá Pilaquinga, Erick Francisco (2023)
The initiative to carry out this analysis and subsequent urban proposal, part of an approach to ordering and planning, which seek to break the fragmentation and segregation that exists in the urban limit of the Huaquillas‘city. Where the physical, environmental conditions and social drastically affect the daily life of this population, therefore an urban integration plan is proposed, which seeks to compact, mix and integrate the study area, “Los Ángeles”, allowing to solve the problems of morphology, mobility and social factor, through a series of proposals that take social urbanism as the main regulator, in addition to intervention in the economic and environmental sector, provides us with guidelines focused on improving the quality of life of those people who for decades have been violated and forgotten , the proposal concludes in improving the connection between the city and the margin, providing basic infrastructure, safe mobility and facilities that promote local commerce and neighborhood development of the place.